Operating Conditions and Composition Effect on the Hydrogenation of Carbon Dioxide Performed over CuO/ZnO/Al2O3 Catalysts - Djaouida Allam; Salem Cheknoun; Smain Hocine (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
A series of catalysts constituted of mixed copper and zinc oxides supported on alumina were prepared by co-precipitation method. The cooper content was in the 10-90 wt.% range. Their catalytic behavior in the hydrogenation of carbon dioxide to methanol was investigated at high pressure (up to 75 bars). The catalysts were characterized by elemental analysis, N2-adsorption, N2O-chemisorptions, and X-ray diffraction (XRD). The catalysts showed a clear activity in the hydrogenation reaction that could be correlated to the surface area of the metallic copper and to the reaction pressure. The CuO/ZnO/Al2O3 catalyst with a Cu/Zn/Al weight ratio of 60/30/10, exhibits the highest carbon dioxide conversion and methanol selectivity. Finally, a mechanism pathway has been proposed on copper active sites of (Cu0/CuI) oxidation state.